2020
DOI: 10.1155/2020/4092470
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Markers in Women with Polycystic Ovary Syndrome

Abstract: Several studies have reported the association between polycystic ovary syndrome (PCOS) and low-grade chronic inflammation to be of uncertain cause: obesity, insulin resistance, or PCOS itself. The aim of the study was to investigate the WBC (white blood cell) count and CRP (C-reactive protein) concentration in women with PCOS and to determine the factors that affect their concentration. The study included 200 women aged 18-40 with PCOS and 105 healthy women as the control group, recruited in the Department of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
78
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(107 citation statements)
references
References 31 publications
10
78
2
3
Order By: Relevance
“…These findings were confirmed by a large number of studies. Elevated CRP levels were found by Tola et al, Souza dos Santos et al, Orio et al, and Rudnicka et al [ 10 , 15 , 16 , 17 ]. In the meta-analysis of 31 clinical trials, conducted by Escobar-Moralle et al, they concluded that CRP in women with PCOS is on average 96 % (95% CI: 71–122%) higher than that in control groups [ 18 ].…”
Section: Inflammatory Markersmentioning
confidence: 94%
See 1 more Smart Citation
“…These findings were confirmed by a large number of studies. Elevated CRP levels were found by Tola et al, Souza dos Santos et al, Orio et al, and Rudnicka et al [ 10 , 15 , 16 , 17 ]. In the meta-analysis of 31 clinical trials, conducted by Escobar-Moralle et al, they concluded that CRP in women with PCOS is on average 96 % (95% CI: 71–122%) higher than that in control groups [ 18 ].…”
Section: Inflammatory Markersmentioning
confidence: 94%
“…According to known data, inflammatory markers or their gene markers are higher in PCOS patients. Correlations have been found between increased levels of C-reactive protein (CRP), interleukin 18 (IL-18), tumor necrosis factor (TNF-α), interleukin 6 (IL-6), and ferritin in the PCOS women compared with age- and BMI-matched controls [ 8 , 9 , 10 ]. Other factors include elevated levels of WBC, plasminogen activator inhibitor PAI1, activity of the angiotensin-renin system (RAS) and free fatty acids (FFA).…”
mentioning
confidence: 99%
“…Chronic low-level inflammation mirrored by elevated levels of pro-inflammatory cytokines, however, is also present in normal-weight PCOS-affected women but was mainly attributed to the fact that also normal-weight PCOS patients tend to have a surplus of visceral adipose tissue and intraperitoneal fat depots [ 61 , 62 ]. Recent studies have identified BMI and insulin resistance as main predictors for increased levels of CRP and white blood cells [ 12 ]. In addition, PCOS patients were shown to have a certain pro-inflammatory genotype characterized by alterations in the genes encoding for TNF-α, TNF receptor and IL-6 [ 63 , 64 , 65 ].…”
Section: Chronic Inflammation In Pcosmentioning
confidence: 99%
“…Furthermore, adipose tissue contributes to constant low-level systemic inflammation as will be described further below in this review. PCOS itself nowadays is considered a condition of chronic inflammation with elevated levels of leukocytes, pro-inflammatory cytokines, elevated white blood count and markers such as the C-reactive protein being detectable [ 12 ] and also affects women with a normal BMI [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 22 ] Inflammatory factors can lead to the reconstruction of ovarian tissue and alter normal follicular development. [ 23 25 ] There is also compelling evidence that the rates of apoptosis of ovarian granulosa cells (GCs) in antral follicles in women with PCOS are significantly increased compared with healthy controls. [ 26 ] Wang et al [ 27 ] suggested that hyperandrogenism is the main cause of infertility as a result of PCOS, hyperandrogenism can drive the generation of the NLRP3 inflammasome, which results in the secretion of inflammatory mediators, and induced low-grade inflammation in mice with PCOS.…”
Section: Nlrp3 and Reproductive Disordersmentioning
confidence: 99%